Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(-12+3-\left|x+2\right|=7-12\)
\(-12+3+12-7=\left|x+2\right|\)
\(\left|x+2\right|=-4\)( vô lý )
Vậy \(x\in\varnothing\)
2) \(\left|x-20\right|-\left(8-7\right)=5-\left|-7\right|\)
\(\left|x-20\right|-1=5-7\)
\(\left|x-20\right|-1=-2\)
\(\left|x-20\right|=-1\)( vô lý )
Vậy \(x\in\varnothing\)
\(a,\left(x-7\right):5=0\)
\(\Rightarrow x-7=0\)
\(\Rightarrow x=7\)
\(b,\left(x:7-7\right)\left(x:12-12\right)=0\)
\(\Rightarrow\hept{\begin{cases}x:7=7\\x:12=12\end{cases}}\)
\(\Rightarrow x=1\)
\(c,300-x:5=273\)
\(\Rightarrow x:5=27\)
\(\Rightarrow x=27.5=135\)
\(d,135+x:2=150\)
\(\Rightarrow x:2=15\)
\(\Rightarrow x=30\)
a) \(\left(x-7\right):5=0\)
\(\Rightarrow x-7=0\times5\)
\(\Rightarrow x-7=0\)
\(\Rightarrow x=0+7\)
\(\Rightarrow x=7\)
Vậy x = 7
b) \(\left(x:7-7\right)\left(x:12-12\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x:7-7=0\\x:12-12=0\end{cases}}\Rightarrow\orbr{\begin{cases}x:7=7\\x:12=12\end{cases}}\Rightarrow\orbr{\begin{cases}x=49\\x=144\end{cases}}\)
Vậy x = 49 hoặc x = 144
c) \(300-x:5=273\)
\(\Rightarrow x:5=300-273\)
\(\Rightarrow x:5=27\)
\(\Rightarrow x=27\times5\)
\(\Rightarrow x=135\)
Vậy x = 135
d) \(135+x:2=150\)
\(\Rightarrow x:2=150-135\)
\(\Rightarrow x:2=15\)
\(\Rightarrow x=15\times2\)
\(\Rightarrow x=30\)
Vậy x = 30
_Chúc bạn học tốt_
( 2 x y + 2/15 ) x 3 = 4/5
( 2 x y + 2/15 ) = 4/5 : 3
( 2 x y + 2/15 ) = 4/15
2 x y = 4/15 - 2/15
2 x y = 2/15
y = 2/15 :2
y = 1/15
(2 x y + 2/15) x 3 = 4/5
2 x y + 2/15) = 4/5 : 3
2 x y + 2/15 = 4/15
2 x y = 4/15 - 2/15
2 x y = 2/15
y = 2/15 : 2
y = 1/15
7/9 x (2 - 1/3 x y) = 14/15
(2 - 1/3 x y) = 14/15 : 7/9
(2 - 1/3 x y) = 6/5
2 - y = 6/5 x 1/3
2 - y = 2/5
y = 2/5 + 2
y = 12/5
4/21 + 5 x y - 8/7 = 1/3
4/21 + 5 x y = 1/3 + 8/7
4/21 + 5 x y = 31/21
5 x y = 31/21 - 4/21
5 x y = 9/7
y = 9/7 : 5
y = 9/35
7/12 x y - 3/12 x y = 5
y x (7/12 - 3/12) = 5
y x 1/3 = 5
y = 5 : 1/3
y = 15
\(\frac{12}{7}\times\frac{2}{11}+\frac{12}{11}\times\frac{15}{7}-\frac{12}{7}\times\frac{6}{11}\)
\(=\frac{12}{7}\times\frac{2}{11}+\frac{12}{7}\times\frac{15}{11}-\frac{12}{7}\times\frac{6}{11}\)
\(=\frac{12}{7}\times\left(\frac{2}{11}+\frac{15}{11}-\frac{6}{11}\right)\)
\(=\frac{12}{7}\times1=\frac{12}{7}\)
\(\frac{12}{7}.\frac{2}{11}+\frac{12}{11}.\frac{15}{7}-\frac{12}{7}.\frac{6}{11}\)
= \(\frac{24}{77}\)+\(\frac{180}{77}\)-\(\frac{72}{77}\)
=\(\frac{132}{77}\)
a) <=> 15-5x-20=-12-3
<=> -5x=-12-3-15+20=-10
=>x=-10:(-5)=2
b)<=>7-x-25-7=-25
<=> -x=-25-7+25+7=0 =>x=0
c) /x+2/=0 => x+2=0 =>x=-2
d) sai đề
e)<=> /x-5/ = 7
<=> \(\orbr{\begin{cases}x-5=7\\x-5=-7\end{cases}}\)
<=> \(\orbr{\begin{cases}x=12\\x=-2\end{cases}}\)
g) <=> -x-20-8+2x=-15
<=> x=-15+20+8=13